Energy consumption and suitability analysis of public transport schemes using econometric modelling and MCDA the case of UP Diliman - Dongallo, Brix P.; Lorenzo, Ruby Joy S.; Seranilla, Justin Jesse L. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Climate change, as well as air pollution, caused by emissions coming from the transport sector has become an issue in the Philippines. The rise in number of vehicles in the country contributes to the rise of CO2 level in the atmosphere, adding more heat-trapping gasses and causing different social and economic problems to the Filipino people. Air pollution has caused significant detrimental impacts to the environment and human health, resulting to millions of pesos in damage. A possible solution to this issue is by improving the transportation decision-making processes. With that, a decision analysis framework with considerations for economic, technical, social, and environmental effects of the status quo and other alternative technologies in the transport sector was demonstrated. Also, it considered the preferences of stakeholders by including their concerns in the decision-making process. The framework, which can be used by planners and decision makers in choosing a transport scheme, was demonstrated in UP Diliman. Conventional and Euro-4 diesel jeepneys and BEMAC e-tricycle were evaluated in this study. Criteria weights were obtained using Simple Multi-attribute Rating Technique Exploiting Ranks (SMARTER) with Rank Reciprocal (RR) method used for subjective weighting, Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) for objective weighting, and combination weighting method. The computed weights and attributes were inputs to the Multi-Criteria Decision Analysis (MCDA) model to obtain each alternative's utility score. Results showed that among the three alternatives, public utility jeepneys (PUVs) had the highest CO2 emission, releasing around 3200 tons a year, consumed the highest amount of energy, with 4.1 million liters of fuel and equivalent cost of 230 million pesos a year, and was the least desirable based on the results of the different MCDA models, except for the jeepney drivers' group. Meanwhile, due to its high attributes, e-trike was chosen as the most suitable transport, with utility scores of 82.65, 79.10, 74.61, and 79.78 % from the MCDA models, respectively. The results can serve as a guide for UP administration when choosing a public transport in the future. The framework can be improved further so that it can be applied to larger areas such as Metro Manila.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Transportation -- Decision making; Transportation -- University of the Philippines